Role of Psychoeducation in Enhancing Young Adults’ Mental Health and Life Adjustment during the Covid-19 Pandemic Research - Ferdous, Jannatul; Roy, Kishor (Jagannath University Journal of Science, 2024)
The ongoing Covid-19 pandemic has a severe impact on people's lifestyles and health all around the world, including Bangladesh. The current study sought to determine if psychoeducation can improve the mental health and life adjustment of young adults in Bangladesh during the COVID- 19 crisis. 30 undergraduate students with high GFQ scores, from two public universities in Dhaka city, were purposefully sampled for the study using a quasi-experimental pretest-posttest design with a control group. The participants were divided into two groups: the experimental group and the control group, each with 15 respondents. The findings of the present study showed the benefits of psychoeducation on the young adults’ mental health and life adjustment. The experimental group's mental health and life adjustment both significantly improved as a result of the psychoeducation intervention, which accounted for 88.8% of the variance in the former and 80.2% in the latter. However, participants who did not receive intervention showed no significant differences in either their mental health or life adjustment. The results may help mental health experts create programs to help young adults who are having problems with their mental health and adjustment. Jagannath University Journal of Science, Volume 10, Number I, Jun 2023, pp. 11−18